Microfluidic electrochemical nitrate sensor using a thin-film copper microelectrode - Cheng, Charmaine (Nanyang Technological University, 2021)
Nitrate exists naturally in the environment, and is mainly used in inorganic fertilizers as a plant nutrient. Meanwhile, contamination of water by nitrate ions has been a persistent problem as a result. The World Health Organization (WHO) guidelines have therefore suggested the maximum nitrate concentration in drinking water at 50 ppm (mg/L). Thus, an accurate, rapid, portable, easy-to-operate and stable nitrate monitoring platform is in need. Electrochemical sensors have been used widely in many industries including environmental, food, pharmaceutical and clinic analysis, etc. In this report, a miniaturized, sensitive and stable electrochemical nitrate sensor has been designed, fabricated and tested. The thin-film copper micro working electrode, platinum pseudo reference electrode, and platinum counter electrode are coated onto a glass wafer. The microchannel is bonded with the glass wafer to create a microfluidic device to allow in-situ flow-through analysis. The amperometry method is employed to determine the nitrate concentration. The as-fabricated device exhibits a wide linear range of 10 μM – 10 mM (0.62 – 620 ppm) with a sensitivity of 0.270 μA μM-1 cm-2 a detection limit of 1.00 μM (S/N = 3).